Early mechanisms of neutrophil activation and transmigration in acute lung injury - Cagle, L. A.; Linderholm, A. L.; Franzi, L. M.; Last, J. A.; Simon, S. I.; Kenyon, N. J.; Harper, R. W. (Frontiers in Physiology, 2022)
Introduction:Neutrophil transmigration is multifactorial and primarily driven by selectins and β2-integrins (CD11b/CD18), whose expression are dependent on the underlying stimulus. Ventilator-induced lung injury (VILI) results in a predominantly CD18-independent mechanism of neutrophil recruitment, while direct endotoxin-induced lung injury results from a CD18-dependent mechanism. We previously observed that lack of NADPH oxidases DUOX1 and DUOX2 resulted in reduced neutrophil influx in a VILI model of lung injury but had no influence on neutrophil influx after LPS exposure. Based on these observations, we hypothesized that DUOX1/DUOX2 are an important component of CD18-independent mechanisms of neutrophil recruitment in the lung. Methods:We exposed Duoxa−/− (KO) mice and Duoxa+/+ (WT) mice to either an intratracheal exposure of lipopolysaccharide (LPS/endotoxin)-or high tidal volume ventilation and compared expression of neutrophil markers between groups. WT mice (129S6/SvEvTac) were obtained from Taconic Biosciences (One Discovery Drive Suite 304; Rensselaer, NY 1244) and were allowed to acclimatize for one week prior to study enrollment. KO mice were generated as previously described [Grasberger 2012] and bred in-house on a 129S6 background. We provided positive-pressure ventilation at a tidal volume of 10 ml/kg with 2 cmH20 positive end-expiratory pressure (PEEP). Mice were assigned to groups consisting of KO (n = 5) and WT (n = 5) in each group and divided into non-ventilated, positive-pressure ventilation, or LPS IT exposure groups. Positive-pressure ventilation was instituted for 4-h using a FlexiVent (Flexiware 8.1, Scireq, Montreal, QC, Canada). Lipopolysaccharide (Salmonella enterica serotype tryphimurium L6143, Millipore Sigma) was administered via an intratracheal (IT) route at a dose of 0.1 mg/kg. Mice were humanely euthanized at 4-h post-injection consistent with the UC Davis IAUCAC-approved protocol. Results:As previously observed, neutrophilic influx into the airways was significantly impaired in the Duoxa−/− (KO) mice after VILI, but not after LPS exposure. LPS-induced lung injury resulted in upregulation of CD11b+ neutrophils and shedding of CD62L and CD162 regardless of DUOX expression, whereas VILI resulted in upregulation of CD49+ neutrophils in the Duoxa+/+ (WT) mice but not the Duoxa−/− (KO) mice. Conclusion:Our data suggest DUOX is required for CD18-independent mechanisms of neutrophil recruitment in the lung induced by acute lung injury, but not for canonical CD18depedent mechanisms after LPS exposure.